Assessing the Shrinkage Cracking Potential of Concrete Using Ring Specimens with Different Boundary Conditions. (7th May 2020) - Menu, Bruce; Jolin, Marc; Bissonnette, Benoit
Abstract : Early-age cracking due to restrained shrinkage affects the performance and service life of concrete structures. Recent studies are successfully making use of the free ring shrinkage test in conjunction with restrained shrinkage measurements for the evaluation of the cracking potential of cementitious materials. This study provides information to improve the interpretation of cracking in ring specimens and a theoretical approach for predicting the stress rate of thick ring specimens. Results show that the rate of strain development and the age-at-cracking vary with specimen drying direction and the exchange surface-to-volume ratio. The results further revealed that early-age shrinkage cracking depends more on the shrinkage rate than the magnitude of the shrinkage itself. Also, it was found that although the restrained ring specimens attained approximately similar strain levels, the cracking age varies significantly, suggesting that elastic stress-strength analysis alone may be inadequate for predicting early-age cracking due to the contribution of creep-relaxation phenomena.